Willful knitting? Contemporary Australian craftivism and feminist histories. Issue 3 (3rd May 2016) - Clarke, Kyra
Abstract: In this article, I connect two contemporary Australian examples of craftivism, Casey Jenkins's performance art piece 'Casting Off My Womb' and the Knitting Nannas Against Gas in Lismore, NSW, to explore histories of feminism, performance art and activism. I argue that these public acts of knitting are disruptive, they challenge expectations and disturb order. I highlight some of the complexities in feminism's relationship with domesticity, noting tensions, but also the ways meanings shift and change. The potential scope of craftivism is rich, with protests spanning from the body and reproductive rights to preventing environmental degradation. In exploring these examples of craftivism, I argue that linking contemporary craftivist practices to histories of feminist activism can highlight the persistence of feminist disturbance across time.